Optimization and economic analysis of liquefaction processes for offshore units. (25th December 2019) - Jin, Chunhe; Son, Heechang; Lim, Youngsub
Highlights: Efficiency and economics were investigated for the offshore liquefaction processes. A dual cycle process shows the best efficiency and total annualized cost. A single cycle process gives the best overall economics for short-term operation. Abstract: The demand to evaluate liquefaction processes applicable to offshore units is increasing with the requirement for offshore platforms. This work investigates both the process efficiency and economic performance of various offshore liquefaction processes. The process schemes include an N2 expander, two types of single mixed refrigerant (SMR), and three different dual mixed refrigerant (DMR) processes. The schemes were simulated with the commercial software Aspen Hysys and optimized to minimize total power consumption as the objective function using a genetic algorithm. Economic and profitability analyses were also conducted for each process to draw a comprehensive economic comparison of the processes. The results show that the SMR process has the lowest total capital cost and payout time, while a DMR presents the best liquefaction efficiency and total annualized cost among the schemes, which are novel outcomes. Therefore, from a long-term economic perspective, the DMR is a good option for long plant operation periods. However, the SMR process shows a net present value 2.17% higher than that of the DMR. In other words, the SMR could be considered as an economical choice for offshore units with short operation period.